The death of things : ephemera and the American novel - Wasserman, Sarah (University of Minnesota Press, 2020)
A comprehensive study of ephemera in twentieth-century literature--and its relevance to the twenty-first century. "Nothing ever really disappears from the internet" has become a common warning of the digital age. But the twentieth century was filled with ephemera--items that were designed to disappear forever--and these objects played crucial roles in some of that century's greatest works of literature. In The Death of Things, author Sarah Wasserman delivers the first comprehensive study addressing the role ephemera played in twentieth-century fiction and its relevance to contemporary digital culture. Representing the experience of perpetual change and loss, ephemera was central to great works by major novelists like Don DeLillo, Ralph Ellison, and Marilynne Robinson. Following the lives and deaths of objects, Wasserman imagines new uses of urban space, new forms of visibility for marginalized groups, and new conceptions of the marginal itself. She also inquires into present-day conundrums: our fascination with the durable, our concerns with the digital, and our curiosity about what new fictional narratives have to say about deletion and preservation. The Death of Things offers readers fascinating, original angles on how objects shape our world. Creating an alternate literary history of the twentieth century, Wasserman delivers an insightful and idiosyncratic journey through objects that were once vital but are now forgotten.